Implementation of SDGs-Based Character Education: Building a Resilient Generation at Khalifah Elementary School Depok - Nurfarah Nidatya; Ayu Wardani; Anindita Lintangdesi Afriani (Universitas Nurul Jadid, 2025)
Awareness of global issues, including the Sustainable Development Goals (SDGs), among primary school children remains relatively low, despite the importance of fostering sustainable development values from an early age. This limited understanding poses a significant challenge within the elementary education environment. In response to this issue, a community service program conducted by a team of lecturers from Universitas Pembangunan Nasional Veteran Jakarta at Khalifah Elementary School, Depok, aimed to enhance students’ awareness and comprehension of global issues encompassed within the SDGs framework.The program employed a combination of lectures, interactive discussions, and demonstrations to introduce key SDG themes, including poverty reduction, health and well-being, quality education, and climate action. Evaluation of the program’s impact was carried out through pre-test and post-test assessments. The results showed a significant improvement in students' understanding, with the average pre-test score being 31.72 and the average post-test score increasing to 53.79. These findings suggest that early educational interventions can play a valuable role in shaping children's perspectives on global challenges and fostering their potential contributions to achieving the SDGs..